Original paperAntiphospholipid syndrome with severe course coexisting with other inflammatory rheumatic diseases in patients hospitalised at the Department of Rheumatology between 2004 and 2005 - Wisłowska, Małgorzata; Dereń, Dorota; Klimowicz, Katarzyna (Reumatologia/Rheumatology, 2007)
The aim of this study was to characterise patients with antiphospholipid syndrome with severe course coexisting with other inflammatory rheumatic diseases, hospitalised at the Department of Rheumatology between 1.04.2004 and 1.12.2005. A group of 14 women was investigated. In 12 cases antiphospholipid syndrome coexisted with systemic lupus erythematosus and with Sjögren’s syndrome in 2 cases. In this article we present clinical symptoms and therapeutic methods.